PENGARUH TERPAAN MEDIA PADA AKUN INSTAGRAM @EXPLORESIAK TERHADAP MINAT KUNJUNGAN WISATA KE SIAK SRI INDRAPURA - Munawwaroh, Putri Raudatul; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Instagram is one of the social media not only to facilitate users to interact with other users, but also can be used as a disseminator of information varied. One form of social media used to disseminate information netizen is Instagram. Instagram accounts that attract much attention of social media users Instagram is an account named @Exploresiak. Instagram account @Exploresiak an Instagram account that provides specific information about the tourist attractions in Siak Sri Indrapura. Exposure to messages on social media into media spread information that could potentially bring interest to visit traveled to the town of Siak Sri Indrapura.The theory used in this research is the theory of SOR. The purpose of this study was to determine how much influence the media exposure @Exploresiak Instagram account of the interests of tourist visits to Siak Sri Indrapura.This reseacrh used quantitative research methods, with data collecting techniques that is through the spreed of online questionnaires using google docs to followers @Exploresiak account with 155 sample counts that are determined through random sampling. The analysis techniques data in this reseacrh using descriptive statistical techniques.Based on these results, the effect of media exposure on @Exploresiak instagram account the interest of tourism in Sri Indrapura Siak it was obtained that regression coefficients value is Y = 10,278 + 0,742 X with a significance level of less than α= 0.05. it means that there is the influence of the effect of media exposure on the Instagram account of the interests of tourist visits @Exploresiak To Siak Sri Indrapura of 50.8% and categorized as moderate, while 49.2% are influenced by other factors not mentioned in the study. This Ho rejected and Ha accepted.Keyword : Exposure, Instagram, Interest